Pengaruh Reward dan Punishment terhadap Kinerja di CV. Jajanan Premium Nusantara - Nur Mira Aisyah; Andi Batary Citta; Muhammad Basri (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The purpose of this research is to determine the effect of reward and punishment on employee performance at CV. Premium Indonesian Snacks. The informants in this research were all CV employees. Premium Nusantara snacks with a sample of 49 people. In determining the sample the author uses a saturated sample, that is, if all members are included as a sample. The data collection techniques used in this research were observation, questionnaires and interviews. The analytical assistance method used is simple linear regression with SPSS 20. The results of this research show that Reward and Punishment together or simultaneously have a positive and significant effect on employee performance at CV. Premium Indonesian Snacks.